Novel Biomarkers for Early Detection of Acute Kidney Injury: A Multi-center Prospective Study - Gupta, Sushrut; Bariar, Hardeep; Kumar Pandey, Santosh; Sharma, Medhavi (Journal of Neonatal Surgery, 2025)
Background: Acute kidney injury (AKI) is a common and serious clinical condition associated with high morbidity, mortality, and healthcare costs. Traditional diagnostic markers such as serum creatinine and urine output demonstrate limited sensitivity and specificity for early AKI detection, delaying diagnosis and potentially missing the therapeutic window for effective intervention. This study aimed to evaluate the performance of novel biomarkers, individually and in combination, for early AKI detection across diverse clinical settings. Methods: In this prospective multi-center study, we enrolled 60 adult patients at risk for developing AKI, stratified across four common clinical scenarios: cardiac surgery (n=15), contrast-induced nephropathy (n=15), sepsis-associated AKI (n=15), and nephrotoxic medication exposure (n=15). Seven urinary and plasma biomarkers were measured at enrollment and at multiple timepoints (6h, 12h, 24h, 48h, 72h): neutrophil gelatinase-associated lipocalin (NGAL) in urine and plasma, kidney injury molecule-1 (KIM-1), interleukin-18 (IL-18), tissue inhibitor of metalloproteinases-2 (TIMP-2) and insulin-like growth factor-binding protein 7 (IGFBP7) product, liver-type fatty acid-binding protein (L-FABP), and cystatin C. AKI was defined according to KDIGO criteria. Biomarker performance was assessed using receiver operating characteristic (ROC) curves, and multivariable models were developed to evaluate biomarker combinations. Results: Of the 60 patients, 26 (43.3%) developed AKI within 7 days, with a median time from enrollment to AKI diagnosis of 33.5 hours. At the 6-hour timepoint, urinary TIMP-2×IGFBP7 demonstrated the highest discriminative capacity for AKI prediction (AUC-ROC 0.85, 95% CI 0.76-0.94), followed by urinary NGAL (AUC-ROC 0.83, 95% CI 0.73-0.93) and plasma cystatin C (AUC-ROC 0.81, 95% CI 0.70-0.92). The combination of these three biomarkers significantly improved diagnostic performance (AUC-ROC 0.92, 95% CI 0.85-0.99), and further enhancement was achieved by integrating them with clinical risk factors (AUC-ROC 0.94, 95% CI 0.88-1.00). Distinct biomarker patterns emerged across different AKI etiologies: urinary NGAL performed best in sepsis-associated AKI (AUC-ROC 0.91), KIM-1 in contrast-induced nephropathy (AUC-ROC 0.85), and TIMP-2×IGFBP7 performed consistently well across all etiologies. All biomarkers demonstrated significant positive correlations with AKI severity and were independently associated with increased in-hospital mortality and hospital length of stay. Conclusions: Novel biomarkers, particularly TIMP-2×IGFBP7, urinary NGAL, and plasma cystatin C, can detect AKI significantly earlier than conventional markers across diverse clinical settings. The combination of multiple biomarkers substantially improves diagnostic accuracy, and distinct biomarker patterns emerge across different AKI etiologies. These findings suggest that biomarker panels may enhance early AKI detection, potentially enabling earlier intervention and improved patient outcomes.